Selling of agricultural products via the Internet - Dariusz Strzębicki (Polityki Europejskie, Finanse i Marketing)
The paper discusses examples of the Internet usage as a marketing channel for sale of agricultural products. The paper includes Polish and foreign case studies with description of various forms of electronic sale, both of the B2C and B2B types. The paper discusses operation of various electronic marketplaces and electronic stores of agricultural products. The author also listed advantages and benefits of using electronic agricultural marketplaces for farmers and customers.